Nanogels Containing Foeniculum vulgare Mill. and Mentha piperita L. Essential Oils: Mosquitoes’ Repellent Activity and Antibacterial Effect - Alireza Sanei-Dehkordi; Abbas Abdollahi; Mojdeh Safari; Farnaz Karami; Ghazal Ghaznavi; Mahmoud Osanloo (Interdisciplinary Perspectives on Infectious Diseases)
Foeniculum vulgare Mill. and Mentha piperita L. are two common medicinally important plants with a wide range of biological activities such as insecticide and antibacterial effects. In this study, the chemical composition of their essential oils was investigated using GC-MS analysis. After that, their nanoemulsions were prepared; optimum samples with droplet sizes of 74 ± 7 and 136 ± 5 nm were gelified. The viscosity of the prepared nanogels and the successful loading of the essential oil in them were investigated. The efficacy of the nanogel containing M. piperita essential oil as a repellent and antibacterial agent was more potent than the nanogel containing F. vulgare essential oil. Its completely protected time against Anopheles stephensi, the main malaria mosquito vector, was 120 ± 8 min. Moreover, the growth of Escherichia coli and Staphylococcus aureus after treatment with 5000 µg/mL of nanogel containing M. piperita essential oil was reduced by 100 and 65%, respectively. Considering natural constituents, a straightforward preparation method, and high efficacy, the nanogel containing M. piperita essential oil could be introduced for further investigation against other mosquitoes and bacterial species.